Mechanochemical synthesis of CaTiO3 from CaCO3-TiO2 mixture - Vukotic, V. M.; Sreckovic, T.; Marinkovic, Z. V.; Brankovic, G.; Cilense, M.; Arandjelovic, D.; Uskokovic, D. P.; Milonjic, S. K.; Rakovic, D. I. (Trans Tech Publications Ltd, 2004)
The synthesis of calcium titanate, CaTiO3, was performed by mechanical activation and thermal treatment. Milling for up to 360 minutes in a planetary ball mill mechanically activated an equimolar mixture of CaCO3 and TiO2 powders. A small amount of mechanically activated mixtures was pressed into briquettes and calcined at 850degreesC for two hours. The effect of mechanical activation on the solid-state reaction was studied using X-ray powder diffraction and differential thermal analysis. The change of morphology and size of powder particles due to milling, were determined by SEM, while BET analysis was used to determine the specific surface area of the powder. The sintering process was followed by a dilatometer during thermal treatment up to 1300degreesC. The main conclusion of the analysis of conducted investigations is that CaTiO3 ceramics can be obtained from an activated mixture at a much lower temperature than reported in the literature owing to acceleration of the chemical reaction and sintering.
Keywords: CaTiO3; mechanochemical synthesis; planetary ball mill